2020
DOI: 10.3389/fpsyt.2020.568329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlation of Anxiety, Insomnia and Somatic Symptoms in a Chinese Population During the COVID-19 Epidemic

Abstract: Background: Anxiety has been a common mental state during the epidemic of Coronavirus Disease 2019 (COVID-19) and is usually closely related to somatization. However, no study on somatization in anxiety and its relationship with insomnia has been conducted. Therefore, this study aimed to identify the prevalence of anxiety, somatization and insomnia and explore the relationships between different psychological states in the general population during the COVID-19 outbreak. Methods: A total of 1,172 respondents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
5
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 50 publications
8
52
5
3
Order By: Relevance
“…In our study, a significant number of patients reported worse pain or psychological distress during the pandemic. This phenomenon is not surprising and has been reported by different authors, as previous pandemics already showed negative effects on psychologi-cal distress of the normal population or mentally prestressed patients (12,(27)(28)(29)(30)(31). Also, other life-threatening events, such as war or terrorism, have proven influence on pain and psychological distress (32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 54%
“…In our study, a significant number of patients reported worse pain or psychological distress during the pandemic. This phenomenon is not surprising and has been reported by different authors, as previous pandemics already showed negative effects on psychologi-cal distress of the normal population or mentally prestressed patients (12,(27)(28)(29)(30)(31). Also, other life-threatening events, such as war or terrorism, have proven influence on pain and psychological distress (32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 54%
“…This is not surprising, given the well-established association between sleep and psychopathology during the pandemic previously reported. ( Hetkamp et al, 2020 ; Huang et al, 2020 ; Stanton et al, 2020 ) Previous studies have shown that sleep and affective brain functioning are linked. ( Palmer and Alfano, 2017 ) Sleep disturbances also increase the risk of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…A high overall score indicates a high level of anxiety. Anxiety levels are defined according to the total score as follows: minimal anxiety (0-7), mild anxiety (8)(9)(10)(11)(12)(13)(14)(15), moderate anxiety (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and severe anxiety (26-63) [17]. A validated Brazilian Portuguese version of the BAI with adequate internal consistency (0.88-0.92) was used in this study [18,19].…”
Section: Questionnaires' Applicationmentioning
confidence: 99%
“…This outbreak is leading to additional worldwide health problems, such as stress, anxiety, depressive symptoms, insomnia, denial, anger and fear [ 7 , 8 , 9 , 10 , 11 ]. The COVID-19 pandemic has also increased anxiety among the pregnant population [ 12 ].…”
Section: Introductionmentioning
confidence: 99%